Macroeconomic Analysis of Mining Stock Index Volatility in Indonesia - Asterina Anggraini; Gatot Nazir Ahmad; Rida Prihatni (International Journal on Advanced Science, Education, and Religion, 2021)
The purpose of this study is to analyze the influence of macroeconomic variables, such as, exchange rates, interest rates, inflation rates, and consumer price index on mining stock volatility. The unit of analysis is the mining stock index volatility in Indonesia from January 2010 to December 2019. The analytical method used in the study is the econometric model ARCH/GARCH using EViews software. The test results show the exchange rate of the dollar against the rupiah (USD/IDR) and the inflation rate has a negative and significant effect while the interest rate and the consumer price index have a positive and significant effect on mining stock index volatility in Indonesia. In addition, based on the ARCH/GARCH coefficient is found that the mining stock index in Indonesia is influenced by the volatility of the current and past stock indexes. The mining stock index volatility in Indonesia is persistent volatile, which is high volatility and occurs continuously. Keywords: Macroeconomic Analysis, Minix Stock Index, Index Volatility